The Study of Coordinate-Wise Decomposition Descent Method for Non-Stationary Optimization Problems - Chang, S. S.; Salahuddin; Wang, L.; Wu, D. P.; Ma, Z. L. (Discontinuity, Nonlinearity, and Complexity, 2026)
The main purpose of this paper is to study a class of non-stationary optimization problem whose objective function need not be smooth in general and only approximation sequences are known instead of exact values of the functions. In our article we presented a coordinate-wise descent splitting method for non-stationary decomposable composite optimization problem and proved convergence of the problems involving the non-smooth set-valued functions. In our paper we gave a general iterative method and proved an existence result of solution for the non-stationary generalized mixed variational inequality problems.